Institutional drivers of crowdfunding volumes - Mari-Liis Kukk; Laivi Laidroo (Journal of Risk and Financial Management, 2020)
Crowdfunding improves access to financing, yet cases of crowdfunding's importance, besides traditional financing, are rare and notably localized. In explaining why global crowdfunding volumes are so heterogeneous, previous academic research has focused mainly on the existence of a legal system that is supportive of crowdfunding, but with conflicting results. We argue that a broader range of institutions must be considered to describe the spread of crowdfunding at its current early stage of development, and provide first empirical evidence on the matter. Using a dataset covering crowdfunding volumes of 122 countries over the years 2015-2016, we confirm that the existence of crowdfunding-specific regulations has a positive association with total crowdfunding volumes per capita. We also find that regulation targeted at a specific type of crowdfunding has an economically stronger association with corresponding transaction volumes. In line with our argument, we find that a significantly broader range of less crowdfunding-specific institutions exhibit strong ties to crowdfunding volumes, with strong e-service culture emerging as an especially robust determinant of all types of crowdfunding volumes. Stronger legal rights, greater financial freedom, and higher democracy levels are also associated with greater total crowdfunding volumes, but exhibit varying relevance across different types of crowdfunding.
Keywords: 330; crowdfunding; financing; institutions; regulations; norms; culture